Optimizing Postpartum Depression Prevention in Primary Health Care Services - Ashifa, Ade Nurul; Nafiani, Elvira; Septiana, Krisna Siska; Adnani, Qorinah Estiningtyas Sakiah; Susiarno, Hadi (Jurnal Kesehatan, 2024)
Post-partum depression (PPD) is a post-natal disorder that not only impacts the mental health of the mother but also has long-term effects on the development and well-being of the child and family. PPD is a preventable disorder, starting from interventions at primary health care facilities. As one of the developing countries with a PPD incidence of 22% per 100,000 births, PPD is considered an urgent public health issue in Indonesia. In practice, evaluation, and improvement of services at primary health care facilities are needed. This study aims to identify and adapt international intervention strategies to reduce post-partum depression prevalence in Indonesian primary health care. A scoping review analysis method was used, involving previous studies on activities from pregnancy to post-partum that can prevent and reduce post-partum depression. The reviewed articles employed Randomized Controlled Trials or Randomized Clinical Trials (RCT) methods with specific inclusion and exclusion criteria. Data were collected from relevant sources, and a synthesis was conducted on 16 articles that met the inclusion criteria. The results show that direct psychological support activities (through health professionals or groups) and indirect support using digital platforms and applications are effective in reducing depression. Strategies such as digital technology, direct support programs, physical therapy, pharmacological therapy, community involvement, and strengthening health services, particularly post-partum psychological counseling, are recommended to enhance prevention. This research supports the expansion of evidence-based strategies that can be implemented in primary healthcare facilities to address post-partum depression.